Determinants of Work Motivation and It’s Implication on Performance of Permanent Lecturers of Private Universities with Accreditation Institution A in Kopertis Region III - Haji, Wachyu Hari (International Review of Management and Marketing, 2018)
The purpose of this study was to determine and analyse the determinants of work motivation and implication on the performance of Permanent Lecturer Private University with Accreditation Institution A in Kopertis Region III. The method used was quantitative research. The study population was all Permanent Lecturer Private University With Accreditation Institution A in Kopertis Region III totally 4225 people, with sample of research 365 respondents that was taken using proportional random sampling technique. Data were collected through research instruments to validity test of instrument using KMO (Kaiser-Meyer-Olkin) technique and to reliability test of instrument using Alpha Cronbach technique. While data analysis using Structural Equation Model (SEM). The result showed that leadership, organizational culture, and work engagement had both positive and significant influence on work motivation both partially and simultaneously. The most dominant variable that influences work motivation is leadership. Furthermore, partially and simultaneously exogenous variables of work motivation as a mediating variable have positive and significant influence on Performance of Permanent Lecturer Private University With Accreditation Institution A in Kopertis Region III with contribution 81%, while the rest is contributed by other variables that was not observed. The most dominant variable that influences performance is organizational culture, while leadership and organizational culture directly influence on performance and need to be considered and enhanced to improve employee performance of permanent lecturers. Keywords: Leadership, Organizational Culture, Work Engagement, Work Motivation, Performance Lecturer. JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7107